Characterization of barium titanate: BaTiO3 (BT) ceramics prepared from sol-gel derived BT powders - Deshpande, S. B.; Godbole, P. D.; Khollam, Y. B.; Potdar, H. S. (Journal of Electroceramics, 2005)
Sol-gel synthesis was attempted at room temperature by adding drop wise a clear solution (made by reacting BaCO3 with glacial acetic acid) to an equi-molar solution of titanium tetrabutoxide in isopropanol (IPA) and acetic acid. The gelation occurred within 30 minutes. The as-dried gel was calcined at 750 degrees C/6 h in air to obtain carbon free BaTiO3 powders. The resulting BT powders were further pressed into pellets and sintered at 1280 degrees C/4 h in air to get dense ceramics (density similar to 94%). XRD and SEM techniques were used for phase and microstructure analysis respectively. The room temperature relative permittivity (e) of 1280 increased to 7200 (at Curie temperature of 127 degrees C) at 1 kHz frequency. The dissipation factor (tan delta) similar to 1.6% was observed in these samples. Also, the ferroelectric properties such as spontaneous polarization (Ps similar to 13 mu C/cm(2)), coercive field (E-c similar to 4.0 kV/cm) and dielectric strength (similar to 34 kV/cm) are estimated for these samples. These performance parameters are compared with the available standard data from the literature.
Keywords: barium titanate; ferroelectricity; Microstructure; relative permittivity; sol-gel processing

Deposition and characterization of silver nano-films by a novel solid liquid interface reaction technique (SLIRT) - Godbole, P. D.; Mitra, A.; Pasricha, R.; Mandale, A. B.; Patil, K. R. (Materials Letters, 2005)
Solid-liquid interface reaction technique (SLIRT) is used to deposit silver film on glass substrate. The solid film of silver nitrate is formed by modified spin coating method. This film is subsequently processed by dipping it in a reducing solution so as to initiate a reaction at the interface and ultimately transform it to totally silver film. In situ transformation of silver nitrate to silver is studied with respect to time spectrophotometrically. The characterization of silver film is done by various physicochemical techniques namely XRD, XPS, ED, TEM and UV visible spectroscopy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; Nano-Particles; solid-liquid interface reaction; thin film

Field emission from oriented tin oxide rods - Deshpande, A. C.; Koinkar, Pankaj M.; Ashtaputre, S. S.; More, Mahendra A.; Gosavi, S. W.; Godbole, P. D.; Joag, Dilip S.; Kulkarni, S. K. (Thin Solid Films, 2006)
Tin oxide (SnO2) films were grown on silicon substrates by a wet chemical route. It was found from scanning electron microscopy investigations that oriented SnO2 rods normal to the substrates were obtained. Field emission studies were carried out in diode configuration in an all metal ultra high vacuum chamber at a base pressure similar to 1.33 x 10(-8) mbar. The `onset' field required to draw 0.1 mu A/cm(2) current density from the emitter cathode was found to be similar to 3.4 V/mu m for SnO2 rods. The field emission current and applied field follows the Folwer-Nordheim relationship in low field regime. The observed results indicate that the field emission characteristics of chemically grown SnO2 structures are comparable to the vapor grown nanostructures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: field emission; microstructures; scanning electron microscopy; tin oxide